Peran Psikologi dalam Pengelolaan Stres pada Mahasiswa Program Studi Pendidikan Keagamaan Buddha - Kelvin Kelvin; Partono Nyanasuryanadi (Institut Nalanda, 2024)
The existence of Buddhist students who experience academic stress in Buddhist religious education study programs is the reason researchers research academic stress in Buddhist students and its impact on student learning outcomes. Psychology as a broad science has many important tasks in human life. In this case, the role of psychology can certainly influence student stress management. From the role of psychology in managing student stress, we know what factors cause stress in students, what the negative impact of stress is, what role psychology plays in managing student stress, and what aspects constitute social support in managing student stress. The aim of research (1) is to explain the causes of academic stress among Buddhist students. (2) analyze the role of psychology in stress management. This research uses a literature review. Case study approach. Research data was collected through a literature review. Data validity using triangulation. The research results show that students experience obstacles in their learning process as follows: Parental demands and academic stress influence learning outcomes such as negative stress and positive stress.